A percepção ambiental dos pescadores da lagoa do Apodi-RN - Nobre, Samilly Brito (Universidade Federal Rural do Semi-Árido, 2018)
The main objective of this work is to diagnose the fishing activities in Apodi - RN Lagoon and, as specific objectives: to identify the socioeconomic profile of the fishermen of Apodi - RN Lagoon, to carry out the characterization of the environmental practices and to point out the environmental perception of the others cases, and to identify the main environmental problems, difficulties and desires related to fishing pointed out by the community. As a methodological procedure, a semi-structured questionnaire was used, and the sampling process was random. By tracing the socioeconomic profile of the fishermen who use the lagoon, it was possible to verify profiles of low schooling and income, but that did not influence the environmental awareness of the individuals. It was analyzed that fishermen, for the most part, are fully aware of the socio-environmental problems that have been increasing over the years with the effects of pollution. After the environmental perception was drawn, the interviewed fishermen report shows that the greatest source of pollution of the lagoon comes from the effluent discharge, altering the water quality and negatively influencing the quality of the fish caught. The population surveyed yearns for several improvements in the lagoon that compete with the local public power, such as better planning of basic sanitation and greater periodicity in the cleanings made in the lagoon.
Keywords: Recursos hídricos; Pesca artesanal; Práticas ambientais; Water resources; Artisanal fishing; Environmental practices; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA